If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 + 8x = 60 Reorder the terms: -4 + x + 8x = 60 Combine like terms: x + 8x = 9x -4 + 9x = 60 Solving -4 + 9x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = 60 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 60 + 4 9x = 60 + 4 Combine like terms: 60 + 4 = 64 9x = 64 Divide each side by '9'. x = 7.111111111 Simplifying x = 7.111111111
| 3-7n+5n=7-52 | | 1.6x+0.25(16-x)=0.26(-16) | | x=5+3x | | 5.379+3.001x=10.429 | | 4y-9+y+46=8y+40-6y | | 5(2x-4)=4(2x+1) | | 8+0.09x=14 | | 14-2.2x=-8 | | -16+7k=k-2k | | 6x+3+2x=5x-4 | | -16k+7k=k-2k | | 7.2x-4.9=60.1 | | (32x^2-8x+4)=0 | | 3/7-3x | | (x+5)(x+2)=25 | | 5x^2+2Y^2+2xy-2x-4y+2=0 | | 4x+5+2x+12=180 | | 2x^2+5y^2=16 | | a^2+b^2=625 | | 7(z+3)-3z=44 | | 10+15y=3y | | Sin(3x)+sin(9x)= | | 9-y=15-5y | | 7-y=3-3y | | Sin(4x)cos(2x)= | | 4+3y=5y | | y=3x^2-17x+10 | | x*ln((8*x^3))+ln((8*x^2))=20-ln(2) | | 72=-16x^2+64x+12 | | 1x=8y+48 | | 2x/2-3x | | 0=-16x^2+64x+8 |